2021
DOI: 10.1186/s12903-021-01446-x
|View full text |Cite
|
Sign up to set email alerts
|

Root canal curvature as a prognostic factor influencing the diagnostic accuracy of radiographic working length determination and postoperative canal axis modification: an in vitro comparative study

Abstract: Background Radiographic analysis of tooth morphology is mandatory for accurate calibration of the degree of canal curvature angle and radiographic working length to its real dimensions in case difficulty assessment protocols. This study aimed to determine the impact of the degree of root canal curvature angle on maintaining the real working length and the original canal axis of prepared root canals using a reciprocating rotary instrumentation technique. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Although canal transportation was induced during the cutting action for the enlargement of the root canal, the shape of the simulated root canals was not significantly modified from the original trajectory. These results are similar with other studies on human teeth regarding canal transportation and centring ability of NiTi instruments, which concluded that they tend to preserve the natural shape of the root canals [33,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although canal transportation was induced during the cutting action for the enlargement of the root canal, the shape of the simulated root canals was not significantly modified from the original trajectory. These results are similar with other studies on human teeth regarding canal transportation and centring ability of NiTi instruments, which concluded that they tend to preserve the natural shape of the root canals [33,34].…”
Section: Discussionsupporting
confidence: 91%
“…Data obtained in the present study, after evaluating the three endodontic shaping systems included in this research, revealed minor mean values of the curvature angle variation ranging from 0.95 • to 2.58 • . These results are comparable to those of other investigations in which the experimental studies were conducted under similar settings as in the present one [34]. However, no comparison was found in the literature between the three shaping systems included in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In their study, GT files have shown a slight enlargement over instrumentation toward the inner side in the beginning of curvature [10]. Faraj B. determines that there is no statistically significant difference between the diagnostic and postinstrumental working length when using files with reciprocating rotation such as WaveOne Gold [11].…”
Section: Discussionmentioning
confidence: 95%
“…The teeth were then stored in normal saline (Marksans Pharma Ltd, India) until the moment of use. 9 The inclusion criteria included extracted human maxillary first molar teeth with MB roots with moderate curvature (10-25°), mesio-buccal roots with (type 1: canal configuration), teeth without root caries, crack, fracture, or internal and external root resorption. The maxillary first molar teeth were selected from patients aged (30 to 40).…”
Section: Sample Preparationmentioning
confidence: 99%